Digitalisation success in learning organisation: preliminary outlook / Roozita Maskun and Norzanah Matt Nor - Maskun, Roozita; Matt Nor, Norzanah (Penerbit UiTM (UiTM Press), 2018)
The use of digital information tools in our daily life, demands technical competencies to navigate through digital information successfully. Every learning organisation today, facing a lot of challenges to keep their institutions going, increasing in growth and sustainable effectively in a modest world. Knowledge is the main resource and the important essence in any of learning organisations. Knowledge management nowadays is practically accessible through digital tools. The need on which digital competency level and resources availability, are the key factors on digitalisation success process. This only a concept paper, hence the purpose of this paper is to reveal that in a learning organisation, the digitalisation process maybe success with the help of technology, resources and the competences of the users. The concept is developed by an extensive literature review of on digitalisation and analysis of different knowledge sources in a learning organisation. The key concept can be used by practitioners in developing a learning organisation to guide them to choose a sufﬁcient subset of tools that covers the digitalisation processes to ensure that no process is overlooked. The result of successful digitalisation is an interesting area for further research. However, the current view on value underlies in it offering practitioners in giving at least a starting point. The paper can be used by educational organisations to guide on successful in digitalisation process effectively and efﬁciently. The paper addresses some of the social elements related to successful in learning organisations. However, it is more technically targeted. Researchers have analysed that holistic overview and the effect of digital competence towards the successful of digitalisation process. Furthermore, limited research addresses the successful of digitalisation process because of the constrains in resources.